2020
DOI: 10.30919/esfaf1115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Classification Efficiency of Self-organizing Map, Principal Component Analysis, and Hierarchical Cluster Analysis for Normal Dairy and Differently Pineapple Fortified Rasgulla

Abstract: Rasgulla, the popular Indian dairy-based dessert, was fortified by using pineapple to improve its nutritional and different physical parameters like color, texture and sensory attributes. Being a highly nutritious, palatable fruit with excellent flavor and visual color characteristics, pineapple fortification provides an edge over normal dairy rasgulla. Comparative analysis of nutritional, X-ray diffraction, texture and sensory characteristics for normal rasgulla sample and pineapple with different drying proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…This might be explained as, because of the incorporation of higher moisture from pineapple fruit pulp (80.78 ± 3.2 %) and differently dried pineapple pulp as well. According to different literature, the ash content of normal rasgulla was varied in the range of (0.75 ± 0.005–1.04 ± 0.03) % [ 12 , 13 ] and in this study, the ash content of NR was found 1.19 ± 0.03 %.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…This might be explained as, because of the incorporation of higher moisture from pineapple fruit pulp (80.78 ± 3.2 %) and differently dried pineapple pulp as well. According to different literature, the ash content of normal rasgulla was varied in the range of (0.75 ± 0.005–1.04 ± 0.03) % [ 12 , 13 ] and in this study, the ash content of NR was found 1.19 ± 0.03 %.…”
Section: Resultssupporting
confidence: 48%
“…Moisture content (MC) and crude protein of samples were estimated as per AOAC 2000 [ 12 ]. Carbohydrate, fat and ash content were measured according to Sarkar et al., 2020 [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise in YI with an increase in temperature might be due to the degradation of color pigments, carotenoids, and xanthophylls. These color pigments start degrading above 50°C temperature (Sarkar et al., 2020). When sugar in pineapple juice is exposed to high temperatures, it caramelizes, changing the yellowish color of pineapple to an orangish red color (Assawarachan & Noomhorm, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Sarkar et al [ 32 ] compared the classification efficiency of SOM, PCA, and hierarchical cluster analysis (HCA) in an analysis of the nutritional value, X-ray diffraction properties, texture, and sensory characteristics for normal ”rasgulla” samples and pineapple with different drying process. The authors observed approximately similar trends in the results obtained by the three compared algorithms.…”
Section: Introductionmentioning
confidence: 99%